Dynamics of a Delay-Varying Computer Virus Propagation Model - Jianguo Ren; Yonghong Xu; Yongchang Zhang; Yongquan Dong; Guosheng Hao (Discrete Dynamics in Nature and Society)
By considering the varying latency period of computer virus, we propose a novel model for computer virus propagation in network. Under this model, we give the threshold value determining whether or not the virus finally dies out, and study the local stability of the virus-free and virus equilibrium. It is found that the model may undergo a Hopf bifurcation. Next, we use different methods to prove the global asymptotic stability of the equilibria: the virus-free equilibrium by using the direct Lyapunov method and virus equilibrium by using a geometric approach. Finally, some numerical examples are given to support our conclusions.